The rebirth of radio. - Riezenman, M.J (IEEE spectrum)
IEEE 802.II, the wireless local-area network standard, is one of the hottest product areas at the moment; Bluetooth threatens to become even hotter; Nokia unveiled its self-configuring rooftop RF system for Internet access; and fixed-wireless links are gaining increasing attention as candidate solutions to the Internet's last-mile problem. Advances in microelectronics have made it possible to build complex wireless systems at low enough cost to make them economically viable. These advances, and others on the way, are not only allowing us to realize the well-known advantages of wireless communication, they may also turn out to be the best way to access the Internet in many situations. Besides, some of the cited drawbacks of wireless may not be as serious as they sound or they may be susceptible to treatment by further advances in semiconductor technology. Optical fiber indeed has much greater capacity than radio but not every application needs immense transmission speed. Fiber makes sense at the core of a telecommunications network. Wireless is being touted for the periphery-or for small, self-contained networks-where speed is less important than such factors as mobility, cost and provisioning speed. As for eavesdropping and interference, advanced digital signal processors (DSPs) are already dealing with those problems and promise to do even more